2018
DOI: 10.1186/s12969-018-0245-x
|View full text |Cite
|
Sign up to set email alerts
|

MBL2 gene polymorphism rs1800450 and rheumatic fever with and without rheumatic heart disease: an Egyptian pilot study

Abstract: BackgroundRheumatic fever (RF) is the result of an autoimmune response to pharyngitis caused by infection with Streptococcus pyogenes. RF is most prevalent in Africa and the Middle East. Rheumatic heart disease (RHD) is the most serious complication of RF. Mannose-binding lectin 2 gene (MBL2) has been reported to be correlated with different cardiac conditions. In Egyptian patients as a new studied ethnic population, it is the first time to evaluate the association between MBL2 gene polymorphism rs1800450 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…for the AA genotype of the MBL2, rs1800450 gene. 48 Corroborating with this data, 3 SNPs of our study presented genotypes that might be associated with high MBL tissue expression in the pulmonary alveolar microenvironment.…”
Section: Discussionsupporting
confidence: 78%
“…for the AA genotype of the MBL2, rs1800450 gene. 48 Corroborating with this data, 3 SNPs of our study presented genotypes that might be associated with high MBL tissue expression in the pulmonary alveolar microenvironment.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, recurrent infections may be associated with the polymorphism of codon 54 of the MBL2 gene [183]. MBL2 polymorphism is also suspected to play a role in the pathogenesis of rheumatic heart disease and rheumatic fever [184]. Therefore, the MBL2 gene is suspected to be one of the diagnostic markers of PANDAS.…”
Section: Genetic Approach To Ocd Including Pandasmentioning
confidence: 99%
“…Few studies showed an association between collectin and colin genes polymorphisms and infectious and autoimmune diseases [31][32][33][34][35][36]. It was shown that there are some associations between gene polymorphisms of MBL [37][38][39][40], Ficolin-1 [16], Ficolin-2 [41] [42], and MASP-2 [43] with RF. However, the impact of the colin-3/FCN3 gene on RF and RHD is currently obscure.…”
Section: Introductionmentioning
confidence: 99%